Plastic Pollution and International Law: Towards a Global Treaty? - Muhammad Sohail Anwar; Muhammad Ahsan Iqbal Hashmi; Mehak Ali (Dialogue Social Science Review (DSSR), 2025)
Plastic pollution is rapidly becoming the most ecological pollution that the earth has seen in recent times. There is no place on the earth that is left unpolluted with plastic waste. This waste had penetrated the ecosystems and is now endangering biodiversity, human health, and sustainable development. Public concern has been expanding and is strongly supported by scientific evidence, but when it comes to international legal responses, the condition remains fragmented and insufficient. Current frameworks, like those which are dealing with maritime pollution, hazardous waste, and the movement of materials, are only partial to the problem and do not have the cohesive enforcement mechanisms.As the world is dealing with how big the problem with plastic pollution is and how complicated it is, a wave of energy gathers for a new dedicated, legally binding global agreement to be formed. The call for this treaty is coming from the realization that voluntary actions and national efforts are not enough to deal with the problem that is inherently transboundary and systemic. Such a global treaty can be the force that brings together different legal efforts, can secure accountability, and can create a common vision on how to manage plastics along their life cycle, starting with the production and design, continuing with the use, and finally with the pollution and remediation.This paper explores the gaps in existing international environmental law and evaluates recent developments, including negotiations at the United Nations Environment Assembly (UNEA), that signal the emergence of a new global governance regime. It also considers key principles that should guide the treaty’s formulation, such as common but differentiated responsibilities, equity, and scientific adaptability. Ultimately, the paper argues that a global treaty is not just a legal necessity but a moral imperative, capable of aligning international cooperation with planetary health and intergenerational justice.